Tinjauan Literatur Terkini Tentang Wakaf - Fauzi, Muhammad; Efendi, Faisal; Bundo, Mayang; Eriawati, Yossi; Rahmat, Fawza (Jurnal Iqtisaduna, 2023)
This study aims to review the latest literature on waqf and highlight directions for future research. This research is qualitative research, with the data search method used is literature review. The data source for this research is literature about waqf, which was collected through search in the Emerald data base for the last 20 months (January 2022 – August 2023), by entering the keyword title in the search column "Waqf, Awqaf". This research uses content analysis as a data analysis tool. The findings show that over the last 20 months, 40 pieces of literature on waqf were obtained, consisting of 2 book chapters and 38 journal articles. This literature has studied waqf from various perspectives, in which case we summarize it into sub-categories (streams). Stream 1 is about awarenes, behavior, decisions to donate to waqf, and stream 2 is about innovation, strategy, development models for waqf, and stream 3 is about practice, performance, accountability, governance of waqf, and finally stream 4 is about waqf and socio-economics. However, waqf also faces criticism and is therefore advised to maintain its identity.